Low and high-risk HPV types detected with hybrid capture II (Hc2) in liquid-based cytology (DNS citoliq®) system: experience from the lams (Latin American Screening) study - Longatto Filho, Adhemar; Utagawa, Maria Lúcia; Pereira, Sonia Maria M.; Pittoli, Janaína Érika; Pittoli, Luciana S. Aguiar; Maeda, Marina Y.S.; Loreto, Celso Di; Roteli-Martins, Cecília; Lima, Temístocles P.; Galvane, Janice Olivia; Syrjänen, Kari J. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: hybrid Capture assay associated to liquid-based cytology is believed to be more effcient than conventional smars alone and able toimprove the sensitivity of uterine cervix lesions in screening programs. Objective:the objective of this study was to analyze the detection of low andhigh risk HPV infection with Hybrid Capture II (HC2) assay in Latin American Screening study (LAMS) using the new system of liquid-based cyto-logy DNACITOLIQ®(DIGENE-Brasil) designed for both cytology and molecular studies. Method: the samples were collected prospectively from357 voluntary women examined at Hospital Leonor Mendes de Barros participating in the ongoing LAMS study (INCO-DEV ICA4-CT-2001-10013)during 2002. Samples were collected with the brush of DNA CITOLIQ®system (Digene-Brasil) in direct-to-vial protocol, immediately preserved inthe UCM (Universal Collecting Medium), a universal conservation medium of the system. The material was firstly used for the preparation of thecytological slides. Subsequently, the material was denatured and the HC2 assay for both low- and high-risk HPV types was performed.Results: inthe 11 low-risk HPV-positive cases, cytology was negative for intraepithelial lesions and malignancy in 10 cases and 1 was an invasive carcinoma.HC2 assay for the high-risk HPV types resulted in negative findings in 293 cases, whereas 46 cases were HPV-positive. Of these 46 positive cases,36 presented with normal cytology, 3 were consistent with LSIL, 5 with ASC-US, 1 was ACG and another one was an invasive carcinoma.Altogether, 18/357 (5.0%) cases showed HC2 positivity for both the low- and high-risk HPV types. Conclusions: the results encourage us to explorethe new DNACITOLIQ system in larger series of women with colposcopy and biopsy data available.